The impact of elevated temperature on the macro-nutrients of commercially important marine bivalves: The implication of ocean warming - Liu, Xiaoxia; Huang, Leiheng; Lim, Leong Seng; Hanafiah Fazhan; Karsoon Tan (Taylor & Francis, 2024)
Bivalves are nutritious animal protein source for humans, rich in high quality proteins, lipids, and carbohydrates. Many studies have shown that ocean warming has detrimental effects on the nutritional quality of bivalves. Although a number of studies are available on the effect of ocean warming on the nutritional value of bivalves, this information is not well organized. In this context, the current study provides a critical review of the effects of ocean warming on the nutritional quality of commercially important edible marine bivalves. In general, ocean warming has caused a reduction in the total lipid and carbohydrate content of bivalves, especially those bivalves inhabiting temperate regions. As for protein, there is no general trend in the effects of ocean warming on the protein reserves of bivalves. In addition, the specific effects of elevated temperature on the macro-nutrients of bivalves highly depend on the tissues, sex and developmental stages of bivalves, as well as seasonal factors. This review not only fills in the knowledge gap regarding the effects of elevated temperature on the macro-nutrients of commercially important marine bivalves but also provides guidance for the establishment of bivalve aquaculture and fisheries management plans to mitigate the impact of climate change.